2002
DOI: 10.1292/jvms.64.29
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in Bone Mineral Density, Cross-Sectional Area and Strength at Different Skeletal Sites in Male Rats.

Abstract: ABSTRACT. Age-related changes in bone mineral density (BMD), cross-sectional area and strength strain index (SSI) of the long bones in the limbs and first lumbar vertebra of male Wistar rats were measured by a peripheral quantitative computed tomography (pQCT) method. One hundred and ten rats aged 2-30 months were used. The results indicate that the total (cortical + trabecular), cortical and trabecular BMD values of the metaphysis and cortical BMD values of the diaphysis in the long bones varied for each bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
35
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 19 publications
8
35
0
2
Order By: Relevance
“…Under normal conditions, mature male rats at the age of six to seven months maintain a constant spine BMD (20). In this study, in the absence of a control group, we assumed that vertebral perfusion also remains constant in mature male rats aged of six to seven months.…”
Section: Discussionmentioning
confidence: 99%
“…Under normal conditions, mature male rats at the age of six to seven months maintain a constant spine BMD (20). In this study, in the absence of a control group, we assumed that vertebral perfusion also remains constant in mature male rats aged of six to seven months.…”
Section: Discussionmentioning
confidence: 99%
“…The strength-strain index (SSI) was also calculated by means of the software described in detail in a previous study [17]. Total (cortical + trabecular) BMD, cortical BMD, and…”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported the age-related changes in bone mineral density (BMD), cross-sectional area, and strength strain index (SSI), an indicator of bone fragility, in male rats [17], as rats are widely used for experiments regarding bone disease and for pharmacological tests. Female rats are more frequently used than males, for example, as a model of postmenopausal osteoporosis after ovariectomy treatment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8 This initial phase of rapid bone loss is followed by a gradual decrease of bone mass, which is also observed in normally aging rats. 11,12 Many studies showed regional differences in bone loss, even within bones. 13,14 While almost all trabeculae are lost in the metaphyseal bone of the proximal tibia, hardly any changes have been observed in the epiphysis.…”
Section: Introductionmentioning
confidence: 99%